(untitled) (Globalization and Business, 2023)
The findings presented in this article are to some extent continuation of the previous studies done by Georgian authors on the economy of Georgia using CGE models. The main instrument used in our research is based on a standard model tailored by Hosoe (Hosoe, 2004) to specifics of open small economy and is its modification of a certain kind. Two types of factors of production are used in this model to produce goods and services: labour and capital. The model also includes four types of commodities and production activities: agriculture, industry, construction and services. Under the necessary assumptions and restrictions, our model is a system composed of 99 equations and as many of endogenous variables. 36 of these equations correspond to the peculiarities of domestic production; 13 of them describe the government behavior; 4 characterize the investment demand function; The other 46 equations represent the behavioral characteristics of government, households, and the external sector. The social accounting matrix corresponding to the state of the economy of Georgia in 2019 is specially constructed for our research. To build it, we used the information contained in the Geostat Supply and Use tables (SUT), separate aggregates of national accounts, balance of payments, consolidated budget, and labor force survey data. Parameters of CGE model are calibrated based on the social accounting matrix. For this purpose, 2019 is considered as a base year and it is assumed that at that time economy of Georgia was in equilibrium. To define units of measurement for commodities and factors of production we set all prices of initial equilibrium to be equal to 1. Using our estimated model we arrange three different scenarios for the Georgian economy to find out what could have happened after implementing certain economic policies under ceteris paribus. According to the first scenario, the initial equilibrium of the economy is determined as of 2019 and the rate of indirect taxes is reduced by 10%. In the second scenario, we assume that the Georgian lari, has depreciated by 15% against the US dollar under ceteris paribus and we examine the expected results of the event. Lastly, in the third scenario, we assume under ceteris paribus that export increases by 20% and determine the aftereffects of export incentives.